Global Value Chains and Upgrading – Experiences of Hungarian Firms in the Machinery Industry - Éltető, Andrea; Magasházi, Anikó; Szalavetz, Andrea (Competitio, 2015)
Global production networks and global value chains have become widespread today. In these cases firms locate the various stages of their value adding activities across different countries. The activities of global value chains form a new phase of globalization characterized by fragmented production, transfer of technology, and decreasing transport costs (Kaplinsky 2013). Developing countries are involved in these production networks, perceiving this as an important (if not the only) way to develop. The Central European countries have taken an active part in the chains of multinational firms since the nineties. The benefit derived from this participation varies across sectors and firms. In this article we analyze the experiences of Hungarian companies in the machinery industry. The structure of the article is the following. After a description of the basic research question and methodology, a literature review is provided. In the following section we introduce the companies surveyed and review their product-, process- and functional upgrading experiences. Finally, we discuss our findings and suggest some managerial and policy implications. Journal of Economic Literature (JEL) codes: F23, M21